SCARCITY-DRIVEN FOMO MARKETING IN FACEBOOK PROMOTIONAL COPY: A QUALITATIVE CONTENT ANALYSIS OF RETAIL ADVERTISING - Misael Aldo Walangitan; Floren Agensia Sinaga; Bervie Fransel Rondonuwu; Immanuel Christian Pontorondo; Arief Perdana Kumaat (EDUCATIONE, 2026)
Social media retailers increasingly use scarcity-oriented copy to make promotional offers appear urgent, limited, and socially desirable. This study aimed to identify and explain how Fear of Missing Out (FOMO)-related cues are linguistically constructed in Facebook retail promotional copy. A qualitative descriptive content analysis was conducted on 24 purposively selected public Facebook advertisement posts from retail sellers in North Sulawesi, Indonesia. The unit of analysis was each caption or visual-text expression that represented time scarcity, quantity scarcity, or social proof. Data were transcribed, anonymized, and coded using an operational codebook adapted from persuasion and FOMO literature. The analysis identified 29 cue occurrences across the 24 posts. Time scarcity was the most frequent cue with 14 occurrences, mainly expressed through same-day offers, promo deadlines, and limited promotional periods. Quantity scarcity appeared 13 times through remaining-stock statements, limited-unit claims, and first-come-first-served expressions. Social proof appeared only twice and did not stand independently, as both occurrences were combined with time scarcity. These findings indicate that local Facebook retail copy constructs FOMO primarily through temporal and quantitative limitation cues rather than through social validation alone. The study contributes to digital marketing communication by clarifying how scarcity-driven FOMO cues are textualized in local promotional discourse. Its limitation is that it analyzes advertising texts, not consumer responses; therefore, behavioral effects require further research.